EDUKASI DAN PELATIHAN KELOMPOK HIPERTENSI TENTANG TERAPI AKUPRESURE PADA TITIK TAICHONG DAN HEGU ACUPOINT DI WILAYAH KERJA PUSKESMAS MARTAPURA 1 KABUPATEN BANJAR - fratama, ferry fadli; Nurhayati, Nurhayati; Apriansyah, Fajar (UPPM Poltekkes Kemenkes Banjarmasin, 2024)
World Health Organization (WHO) reports that around 26.4% of the world's population experiences hypertension. Based on RISKESDAS (2018), the prevalence of hypertension based on measurement results in the population aged 18 years is 34.1%, the highest in South Kalimantan (44.1%), while the lowest is in Papua (22.2%). It is estimated that the number of hypertension cases in Indonesia is 63,309,620 people, while the death rate due to hypertension in Indonesia is 427,218 deaths. The aim of this community service is to increase the knowledge and skills of the hypertension group regarding hypertension management with acupressure at the thaicong and hegu acupoints. The implementation of this community service activity consists of two activities, namely the first activity of forming a healthy acupressure group and acupressure demonstration at the thaicong and hegu acupoints. The results of this community service are an increase in the knowledge and skills of the hypertension group in hypertension management.